Resource-Based Approaches: A Framework for Analyzing Competitiveness in the Context of Reverse Logistics - Asmaa Bentamar; Kacem Taj; Omar Ourahou (European Scientific Journal, ESJ, 2021)
In a constantly changing society, organizations must adapt and be open to change. Reactivity, variety, costs, deadlines, innovation, increase their competitiveness, increase their flexibility and improve their performance. The approach by resources and capacities is a framework for analyzing competitive advantage. However, the contributions of this approach to the problem of reverse logistics are multiple. The main ambition of this article is therefore to provide a summary of the conceptual contributions. This literature review will allow analysis of the main relationships between resources, capacities and knowledge management and how these approaches can influence the competitiveness of the company, a discussion on the research perspective are presented and conceptual models are proposed.